Speciation in Ancient Lakes 8 – Celebrating 25 years and moving towards the future - Albrecht, Christian; Salzburger, Walter; Tolo, Casim Umba; Stelbrink, Björn (Journal of Great Lakes Research, 2020)
Hypotheses in evolutionary biology, ecology, climatology and geology are often tested in insular ecosystems. Ancient lakes, i.e. lakes that have existed since at least the Last Glacial Maximum and typically for longer periods of time, provide such study sys tems (Brooks, 1950), and awide range of knowledge in the fifield of biotic diversifification stems from the examination of ancient lakes and their biota (Cristescu et al., 2010; Martens, 1997; Rossiter and Kawanabe, 2000, Sturmbauer et al., 2012; von intelen et al., 2014). Scientists fifirst formalized ‘‘Speciation in Ancient Lakes (SIAL)” as a society during an initial workshop held in Belgium in 1993 (Martens et al., 1994). Ever since, SIAL meetings have been organized at various places, not always but often at the shores of the ancient lakes that interest this scholarly community.